2008
DOI: 10.1242/jeb.012617
|View full text |Cite
|
Sign up to set email alerts
|

The lycaenid butterfly Polyommatus icarus uses a duplicated blue opsin to see green

Abstract: SUMMARYThe functional significance of gene duplication is rarely addressed at the level of animal behavior. Butterflies are excellent models in this regard because they can be trained and the use of their opsin-based visual pigments in color vision can be assessed. In the present study, we demonstrate that the lycaenid Polyommatus icarus uses its duplicate blue (B2) opsin, BRh2, in conjunction with its long-wavelength (LW) opsin, LWRh, to see color in the green part of the light spectrum extending up to 560·nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 41 publications
2
43
0
Order By: Relevance
“…True color vision has been demonstrated explicitly for several butterfly and moth species (Kelber and Henique, 1999;Kelber and Pfaff, 1999;Kinoshita et al, 1999;Sison-Mangus et al, 2008), and is likely to be common across Lepidoptera.…”
Section: Color Visionmentioning
confidence: 99%
See 1 more Smart Citation
“…True color vision has been demonstrated explicitly for several butterfly and moth species (Kelber and Henique, 1999;Kelber and Pfaff, 1999;Kinoshita et al, 1999;Sison-Mangus et al, 2008), and is likely to be common across Lepidoptera.…”
Section: Color Visionmentioning
confidence: 99%
“…Butterflies in particular rely on light in a variety of behavioral contexts, and the range of their light perception, which in some taxa extends from ultraviolet through red (300 to 700nm), is among the broadest known in the animal kingdom (Briscoe and Chittka, 2001;Silberglied, 1984). True color vision, the ability to discriminate visual stimuli based on wavelength, independent of intensity, has been demonstrated explicitly for several butterfly and moth species (Kelber and Henique, 1999;Kelber and Pfaff, 1999;Sison-Mangus et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, while butterflies in the genus Papilio use duplicate LW opsins to see green (Kelber, 1999), the lycaenid Polyommatus icarus, uses its duplicate B2 opsin, in conjunction with its LW opsin, to see in the green part of the spectrum extending up to 560 nm (Sison-Mangus et al, 2008). This suggests that natural selection has hit upon alternative strategies for color vision in the green range in lycaenid and papilionid butterflies.…”
Section: Subfunctionalization and Neofunctionalization Of B Opsins Inmentioning
confidence: 99%
“…The red filtering pigments in the eyes of butterflies, however, do not appear to have a unified function. For instance, behavioral tests have shown that the nymphalid Heliconius erato uses a heterogeneously expressed red filtering pigment together with a single LW opsin to produce expanded color vision in the long wavelength range when foraging (Zaccardi et al, 2006), but the lycaenid Polyommatus icarus, which also has a heterogeneously expressed red filtering pigment in its eye, does not appear to have expanded color vision, at least when tested in the context of feeding (Sison-Mangus et al, 2008).…”
Section: Subfunctionalization and Neofunctionalization Of Lw Opsin Exmentioning
confidence: 99%
“…Female Eurema hecuba (Coliadinae: Pieridae) were similarly shown to prefer males with the brightest UV iridescence overlaying a diffuse pigment-based yellow (Kemp, 2007a). Given that many other butterflies have color patches with UV reflectance, and that butterfly color vision systems are astonishingly diverse (Arikawa et al, 2005;Briscoe and Bernard, 2005;Stalleicken et al, 2006;Koshitaka et al, 2008;Sison-Mangus et al, 2008;Chen et al, 2013), it is worthwhile investigating in other species whether it is the UV or the human-visible part of the color patch reflectance spectrum, or both, that is being used for signaling. It is particularly interesting to investigate this question where there has been a phylogenetic transition from using one type of pigmentation to another, as for the yellow wing colors in the passion-vine butterflies of the genus Heliconius Bybee et al, 2012) (see below).…”
Section: Introductionmentioning
confidence: 99%